1980
DOI: 10.1507/endocrj1954.27.supplement_87
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Actions of Glucagon

Abstract: Glucagon (Bromer et al., 1957; Staub et al., 1953), the hyperglycemic-glycogenolytic hormone isolated from the islets of the pancreas has a broad spectrum of gastrointestinal actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This suggests that CCK stimulates the release of PP by act ing via CCK receptors. Since PP is known to affect gastric secretion and gastric emptying [30] it remains to be established what role, if any, PP plays in the action of CCK on gastric functions observed in this report.…”
Section: Discussionmentioning
confidence: 92%
“…This suggests that CCK stimulates the release of PP by act ing via CCK receptors. Since PP is known to affect gastric secretion and gastric emptying [30] it remains to be established what role, if any, PP plays in the action of CCK on gastric functions observed in this report.…”
Section: Discussionmentioning
confidence: 92%
“…Early studies that assessed the effect of intravenous glucagon on esophageal motor function evaluated only the lower esophageal sphincter (LES) resting pressure [2,3]. These studies and others have demonstrated in humans and animals that, after a latency period of 30-60 sec postadministration of glucagon, a significant reduction in LES resting pressure is achieved [2][3][4][5][6][7][8]. The duration of action may last 4-15 min and is probably a dose-dependent phenomena [4].…”
mentioning
confidence: 99%